2021
DOI: 10.3390/ijerph18105478
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Triad of Personality’s Relationship with Compliance towards COVID-19 Pandemic Recommendations along with Anxiety and Depressive Symptoms in Polish Citizens

Abstract: The outbreak of the COVID-19 pandemic forced everyone to comply with rules of a sanitary regime and social distancing on a daily basis. The aim of our research was to assess the differences in the levels of Dark Triad traits between people who obeyed and disobeyed the pandemic restrictions. Additionally, we considered the possible correlation between the Dark Triad and the intensity of symptoms of depression and anxiety. A total of 604 Polish participants, whose average age was 28.95 ± 11.27 years, completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 64 publications
3
17
0
Order By: Relevance
“…The stress they've been exposed to because of this has exacerbated their anxiety in social situations. These findings are in line with (Gogola et al, 2021 ), and contradict (Akehurst and Thatcher, 2010 ; Ali and Chamorro-Premuzic, 2010 ; Lyons et al, 2020 ) because they found that narcissistic personality characteristics such as excessive self-love, adoration, exhibition, and greater self-esteem might shield people against sadness, anxiety, and depression. However, assumption 1b identified an insignificant association between Machiavellianism and anxiety disorder, and this is due to their diverse social networks and considerable immunization power.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The stress they've been exposed to because of this has exacerbated their anxiety in social situations. These findings are in line with (Gogola et al, 2021 ), and contradict (Akehurst and Thatcher, 2010 ; Ali and Chamorro-Premuzic, 2010 ; Lyons et al, 2020 ) because they found that narcissistic personality characteristics such as excessive self-love, adoration, exhibition, and greater self-esteem might shield people against sadness, anxiety, and depression. However, assumption 1b identified an insignificant association between Machiavellianism and anxiety disorder, and this is due to their diverse social networks and considerable immunization power.…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, no study examined ASMR and loneliness concerning dark triad and anxiety disorder. Recent studies were conducted on ASMR, loneliness (Zhang et al, 2015 ), and a study on dark triad and anxiety by Gogola et al ( 2021 ). No study has been undertaken to support the framework described in this article.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the intensity of the Dark Triad correlated with an increased occurrence of depressive symptomatology. Interestingly, higher levels of subclinical narcissism seem to contribute to civil compliance and increased anxiety symptoms [ 95 ]. On the same note, Doerfler et al investigated the role of the Dark Triad traits in engaging risky decision-making during the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…According to the available studies, the prevalence of depressive symptoms in different populations ranged between 14.6% and even 48.3%, while the prevalence of anxiety symptoms oscillated between 6.3% and 50.9% ( 7 ). Study conducted in a group of adult Poles revealed a significant intensification of depressive symptoms among 26% respondents and anxiety symptoms among 63% respondents ( 8 ). It has also been shown that groups particularly exposed to pandemic distress are women, young people (18–29 years of age), people experiencing mental disorders in the past and people from socially disadvantaged backgrounds ( 9 ).…”
Section: Introductionmentioning
confidence: 99%